Sustainable clothing: Why conspicuous consumption and greenwashing matter (2023)
This study analyzes the degree to which conspicuous consumption motives, environmental concern, perceived consumer effectiveness, trust in sustainable clothing brands, and perceived greenwashing trigger the purchase of sustainable clothing. The theoretical framework was tested with a representative online sample of the Australian population (N?=?600). Results showed that all proposed antecedents have a positive relationship with the purchase of sustainable clothing, with the exception of perceived greenwashing, which decreases purchase intention. In addition, perceived consumer effectiveness positively moderated the effect of conspicuous consumption motives on purchasing. Conspicuous consumption motives had a stronger effect on purchase when perceived effectiveness was high, and this influence was reduced for lower perceived effectiveness. The interaction between conspicuous consumption and perceived efficacy had the strongest effect in the model. Our findings highlight the relevance of conspicuous consumption as a motive for switching to sustainable clothing and the likewise important role of perceived consumer effectiveness, which is a boundary condition for this effect. Findings also confirm the significant positive influence of environmental concern and trust in the sustainable clothing brand, while perceived greenwashing is a barrier to the adoption of sustainable clothing. Theoretical and practical implications of the findings are discussed.